2012
DOI: 10.1097/jom.0b013e31825461f4
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Health Effects in Swine Building Workers After Respiratory Protection Use

Abstract: Objective: To compare inflammation and lung function in swine workers after periods with and without respiratory protection during work. Methods: Twenty-three workers were examined before and after two nonprotected work shifts. One shift was preceded by a period with diminished exposure by use of respirators. The other shift was preceded by an unprotected period of work. Results: Endotoxin concentrations were similarly high (24,636 and 28,775 endotoxin units/m 3 ). A 3.1% cross-shift decline in forced vital ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In addition, intermittent use of PPEs has been suggested to cause cross-shift inflammatory and respiratory reactions at return to unprotected work. 182 Besides the high levels of dust and endotoxin exposure, results from the reviewed studies demonstrated high variability of both temporal and personal nature in personal exposure concentrations to dust and endotoxin among livestock farmers. A detailed description of this issue is not within the scope of the present paper.…”
Section: General Discussion and Concluding Remarksmentioning
confidence: 95%
“…In addition, intermittent use of PPEs has been suggested to cause cross-shift inflammatory and respiratory reactions at return to unprotected work. 182 Besides the high levels of dust and endotoxin exposure, results from the reviewed studies demonstrated high variability of both temporal and personal nature in personal exposure concentrations to dust and endotoxin among livestock farmers. A detailed description of this issue is not within the scope of the present paper.…”
Section: General Discussion and Concluding Remarksmentioning
confidence: 95%
“…5,6 Recently, our group found that adaptation was partly lost during the low-exposure summer season 7 or after use of respiratory protection. 8 As part of a study on effects of different work conditions on lung function and inflammation among swine building workers, we investigated plasma levels and white blood cell mRNA expression of selected proteins known to be involved in the response to inhaled endotoxin or swine dust. Our aim was to identify differences in selected mRNAs and some of their proteins known to relate to work in the swine houses on three ordinary workdays preceded by different work conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This association is a potential indication of healthy worker effect bias where only the healthiest and most tolerant of symptoms report for work every day. It may also be due to the fact that when workers are away from work exposures their respiratory system rebounds, leading to inflammatory reactions (Bønløkke et al 2012). Another unexpected finding was that at baseline, workers who reported "always" wearing all three types of PPE at work reported increased odds of allergies.…”
Section: Discussionmentioning
confidence: 98%